STRATEGIC MANAGEMENT IN INVESTING IN BUSINESSES (Лучшие интеллектуальные исследования, 2025)
Abstract. This article analyzes the role and importance of strategic management in the process of investing in enterprises. Long-term strategic planning, risk management, effective resource allocation and innovative approaches are considered as important factors in making investment decisions. Also, suggestions and recommendations are given on improving the efficiency of investments through strategic management tools.